Inflaç\~ao, desemprego e choques cambiais: Novas evidências para o Brasil - Adolfo Sachsida; Mario Jorge Mendonça; Luis Alberto Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– We estimate the Phillips curve with an exchange rate shock to the Brazilian economy. Besides panel data, we estimate the Phillips curve by time series methodology, including Bayesian techniques and Smoothing Transition Regressions (STR) model. The econometric results show three important conclusions: a) we test and confirm the Blanchard and Gali (2007) restrictions over the sum of the coefficients associated with inflation; b) the coefficient associated to the expectation of inflation is greater than the coefficient associated with past inflation (which is in contrast with previous studies to the Brazilian economy); and c) in the short-run both the unemployment rate and the exchange rate shock are not important determinants of current inflation.
Keywords: E31; E24; C33; 330; Phillips-Kurve; Wechselkurs; Schock; Zeitreihenanalyse; Brasilien